PENGARUH PSIKOEDUKASI KELUARGA TERHADAP TINGKAT KECEMASAN DAN KEMAMPUAN KELUARGA DALAM MERAWAT PENDERITA TB DI PUSKESMAS SUMBERMANJING WETAN KECAMATAN SUMBERMANJING KABUPATEN MALANG - Faizatur Rohmi* Setyawati Soeharto** Retno Lestari*** (Universitas Muhammadiyah Jember, 2016)
TB is one of chronic lung infections with at least six months of treatment or medications. International Union against Tuberculosis and Lung Disease states that it must be given immediately to patients or their family members in order to decrease side effect of the disease. IUATLD recommends the patients and their family have to get education about this disease and its treatment. This study aims to get understanding of the influence of family psychoeducation to anxiety level and family’s ability in taking care of TB patient. This study used quasy experimental by using purposive sampling as the sampling technique. The subjects of this study consisted of twenty eight (28) respondents whom divided into control group and experimental group. The data were collected by using questionnaire which had been tested by test of validity and reliability. Based on bivariate analysis using Mann Whitney test shows that significance value of anxiety level (p0.05) and ability (cognitive, affective and psychomotor) (p0.05).It could be concluded that family psychoeducation influenced anxiety level and the ability of family members in taking care of the patient. Based on the result, it needs to apply psychoeducation as caring act to reduce anxiety level and improve family members’ ability in taking care of the patient in psychosocial case.